Genome Doubling Shapes High-Grade Transformation and Novel EWSR1::LARP4 Fusion Shows SOX10 Immunostaining in Hyalinizing Clear Cell Carcinoma of Salivary Gland - Kobayashi, Kenya; Kawazu, Masahito; Yoshimoto, Seiichi; Ueno, Toshihide; Omura, Go; Saito, Yuki; Ando, Mizuo; Ryo, Eigitsu; Sakyo, Airi; Yoshida, Akihiko; Yatabe, Yasushi; Mano, Hiroyuki; et al. (Laboratory investigation, 2023)
Hyalinizing clear cell carcinoma (HCCC) is a rare indolent malignant tumor of minor salivary gland origin with EWSR1::ATF1 rearrangement. Pathologically, the tumor cells possess a clear cytoplasm in a background of hyalinized stroma. Generally, the tumor cells are positive for p63 and p40 and negative for s100 and α-smooth muscle actin, suggesting that they differentiate into squamous epithelium and not into myoepithelium. In this study, we performed a detailed histopathological and genomic analysis of 6 cases of HCCC, including 2 atypical subtypes—a case of “high-grade transformation” and 1 “possessing a novel partner gene for EWSR1.” We performed a sequential analysis of the primary and recurrent tumor by whole-exome sequencing, RNA sequencing, Sanger sequencing, and fluorescence in situ hybridization to investigate the effect of genomic changes on histopathology and clinical prognosis. A fusion gene involving the EWSR1 gene was detected in all cases. Five cases, including the “high-grade transformation,” harbored a known EWSR1::ATF1 fusion gene; however, 1 case harbored a novel EWSR1::LARP4 fusion gene. This novel EWSR1::LARP4–fused HCCC has a SOX10-positive staining, which is different from the EWSR1::ATF1–fused HCCC. According to whole-exome sequencing and fluorescence in situ hybridization analysis, the “whole-genome doubling” and focal deletion involving CDKN2A, CDKN2B, and PTEN were detected in HCCC with “high-grade transformation.” Conclusively, we identified a novel partner gene for EWSR1, LARP4, in indolent HCCC. Importantly, “high-grade transformation” and poor prognosis were caused by whole-genome doubling and subsequent genomic aberrations.